Enhancing students’ listening proficiency (Mahārah Istimā’) in State Islamic Religious Higher Education Institutions by utilising the e-Learning Application “HATI” - Isti Jayang Fitrah; Muhammad Rikza Wahyu Hilal Ramdhani; Laily Fitriani; Abdul Aziz (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study seeks to examine the process and enhancement of listening proficiency (mahārah istimā’) in the Arabic language among students of PKPBA (Special Programme for Arabic Language Development) at Maulana Malik Ibrahim State Islamic University Malang, when utilising the e-learning application HATI (Hayāh Al-‘Arābiyah Tafā’uliyan Iliktruniyan). The researcher utilised a mixed-methodologies technique, integrating both quantitative and qualitative methods and conducting descriptive qualitative and descriptive quantitative analyses. The researcher employed a combination of methodologies, including qualitative descriptive analysis, descriptive statistics, and the paired sample t-test were analysed using SPSS 16. The study focused on the first semester students of PKPBA at UIN Malang and researcher chose a sample of 28 students. The findings suggest that the utilisation of the HATI e-learning application for acquiring mahārah istimā’ can enhance students’ sensitivity and facilitate their ability to listen to Arabic conversations. This, in turn, makes it more pleasurable for students and facilitates the attainment of the predetermined learning goals. This is supported by the t-test value of sig. 0.000 < 0.05, which indicates a statistically significant difference or a substantial influence of using the HATI application on the enhancement of mahārah istimā’. The acquired values consist of an average of 65.00 prior to or in the absence of utilising the HATI application. In contrast, following the utilisation of the HATI application, the mean value was 81.79. The two numbers exhibit a disparity, with an average deviation of 16.79, indicating an improvement in students’ mahārah istimā’ when utilising the HATI e-learning programme.